Penilaian kualitas estetika elemen arsitektural bangunan Kolonial di Jalan Basuki Rahmat, Malang (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Assessment of aesthetical quality of architectural elements of Colonial buildings in Jalan Basuki Rahmat, MalangThe characters of a building are formed by several elements, one of them is an architectural element. The architectural element can be assessed using aesthetic judgment scales. Aesthetic value is closely related to public perception. The Colonial buildings in Jalan Basuki Rahmat have distinctive character that worth to be preserved.  Assessment of building aesthetic is the initial step in the effort to preserve colonial buildings. This study aims to assess the aesthetic quality of the architectural elements of Colonial buildings in Jalan Basuki Rahmat. Questionnaires are used to collect data, and Aesthetic measurement is carried out using the semantic differential scale. The community members are requested to judge the aesthetic quality of the buildings based on their own perceptions by looking at photos. Data were analyzed using descriptive statistics, independent samples test, and linear regression. The research results showed that the architectural element that had the most significant impact on the aesthetic quality of Colonial buildings were the façade. The Colonial building with the highest aesthetic value is the Church of the Sacred Heart of Jesus Malang.
Keywords: Aesthetic; Architectural element; Colonial building